Neural effects of antidepressant medication and psychological treatments: a quantitative synthesis across three meta-analyses. (October 2021) - Nord, Camilla L.; Barrett, Lisa Feldman; Lindquist, Kristen A.; Ma, Yina; Marwood, Lindsey; Satpute, Ajay B.; Dalgleish, Tim
Abstract : Background: Influential theories predict that antidepressant medication and psychological therapies evoke distinct neural changes. Aims: To test the convergence and divergence of antidepressant- and psychotherapy-evoked neural changes, and their overlap with the brain's affect network. Method: We employed a quantitative synthesis of three meta-analyses ( n = 4206). First, we assessed the common and distinct neural changes evoked by antidepressant medication and psychotherapy, by contrasting two comparable meta-analyses reporting the neural effects of these treatments. Both meta-analyses included patients with affective disorders, including major depressive disorder, generalised anxiety disorder and panic disorder. The majority were assessed using negative-valence tasks during neuroimaging. Next, we assessed whether the neural changes evoked by antidepressants and psychotherapy overlapped with the brain's affect network, using data from a third meta-analysis of affect-based neural activation. Results: Neural changes from psychotherapy and antidepressant medication did not significantly converge on any region. Antidepressants evoked neural changes in the amygdala, whereas psychotherapy evoked anatomically distinct changes in the medial prefrontal cortex. Both psychotherapy- and antidepressant-related changes separately converged on regions of the affect network. Conclusions: This supports the notion of treatment-specific brain effects of antidepressants and psychotherapy. Both treatments induce changes in the affect network, but our results suggest that their effects on affect processing occur via distinct proximal neurocognitive mechanisms of action.